Heat transfer enhancement in a rectangular duct by using winglet and nanofluids - Ghitheeth Al-Challabi, Ali Hussein (2014)
The vortex generators induce streamwise longitudinal vortices. These vortices disrupt the growth of the thermal boundary layer and serves to bring about heat transfer enhancement between the fluid and the fin surfaces. The geometrical configuration considered in this study is representative of a channel with winglets spread over three rows each row 13 a pair of winglets. In this study, three dimensional turbulent flow of different nanofluids flow inside a rectangular duct with the existence of vortex generator winglets at different angle are (10º, 20º and 30º ) is numerically investigated. The effects of type of the nanoparticles, and Reynolds number on the heat transfer coefficient and pressure drop of nanofluids are examined. Reynolds numbers (10000, 20000, 30000, 40000 and 50000). A constant surface temperature is assumed to be the thermal condition for the upper and lower heated walls. In the present work, three nanofluids are examined which are Al2O3, CuO and SiO2 suspended in the base fluid of water with nanoparticles concentration ranged ϕ = 4% and the nanoparticles diameter, dp is (30 nm). The validity of the code is tested by comparing the results for a three-dimensional experimental the published results with numerical results. The results are in good agreement with the published results. It is observed from the results that the heat transfer increases with the increase in the angle of attack and Reynolds number. the result reporting showed that the case of channel with winglet at angle 30˚ presented highest heat transfer rate. Where that, the case of channel with winglet at angle 20˚ presented, the Nu values are lower than the winglet with angle 30˚. Also, the case of channel with winglet at angle 10˚ and smooth channel presented, the Nu values are apparently lower than the winglet with angle 30˚.